Implementasi Kebijakan Rencana Detil Tata Ruang (RDTR) Di Kecamatan Balongbendo Kabupaten Sidoarjo (Studi Pelanggaran Ijin Pemanfaatan Ruang) - Dody Feryanto Kurniawan; Cahyo Sasmito; Cakti Indra Gunawan (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2021)
This study was conducted to find out how the Implementation of the Detailed Spatial Planning (RDTR) Policy in Balongbendo District, Sidoarjo Regency uses an approach to space utilization violations. The research was conducted using qualitative research methods in Balongbendo District, Sidoarjo Regency. Determination of informants using purposive sampling and data analysis is done by data reduction, data presentation and drawing conclusions. The results of the study show that the implementation of the RDTR Policy in Balongbendo District has been going well, seen from various space utilization permits such as permits for housing development, industry, trade and service activities, shophouse construction and so on. The supporting factors are good cooperation between policy implementing agencies, socialization of RDTR policies, socialization of RDTR policies to the community, seriousness and consistency of RDTR policy implementation, while the inhibiting factor is public understanding of the importance of implementing RDTR policies. community is not evenly distributed, lack of supervision on space utilization activities, there are still acts of violation of RDTR provisions.